A cost effectiveness study establishing the impact and accuracy of implementing the NICE guidelines lowering plasma NTproBNP threshold in patients with clinically suspected heart failure at our institution. (15th April 2018) - Webb, Jessica; Draper, Jane; Rua, Tiago; Yiu, Yee; Piper, Susan; Teall, Thomas; Fovargue, Lauren; Bolca, Elena; Jackson, Tom; Claridge, Simon; Sieniewicz, Ben; Porter, Bradley; et al.
Abstract: Aims: The 2014 National Institute of Clinical Excellence (NICE) guidelines on the management of acute heart failure recommended using a plasma NT-proBNP threshold of 300 pg/ml to assist in ruling out the diagnosis of heart failure (HF), updating previous guidelines recommending using a threshold of 400 pg/ml. NICE based their recommendations on 6 studies performed in other countries. This study sought to determine the diagnostic and economic implications of using these thresholds in a large unselected UK population. Methods: Patient and clinical demographics were recorded for all consecutive suspected HF patients over 12 months, as well as clinical outcomes including time to HF hospitalisation and time to death (follow up 15.8 months). Results: Of 1995 unselected patients admitted with clinically suspected HF, 1683 (84%) had a NTproBNP over the current NICE recommended threshold, of which 35% received a final diagnosis of HF. Lowering the threshold from 400 to 300 pg/ml would have involved screening an additional 61 patients and only would have identified one new patient with HF (sensitivity 0.985, NPV 0.976, area under the curve (AUC) at 300 pg/ml 0.67; sensitivity 0.983, NPV 0.977, AUC 0.65 at 400 pg/ml). The economic implications of lowering the threshold would have involved additional costs of £42, 842.04 (£702.33 per patient screened, or £ 42, 824.04 per new HF patient). Conclusion: Applying the recent updated NICE guidelines to an unselected real world population increases the AUC but would have a significant economic impact and only identified one new patient with heart failure.